IMPROVING STUDENTS’ LISTENING COMPREHENSION BY MEANS OF DICTOGLOSS TECHNIQUE - Darsih Riestiani (Journal of English Education Program (JEEP), 2015)
This paper reports on the implementation of using dictogloss technique in improving students’ listening comprehension. This study was aimed at finding out the differencess between students’ who are taught by using Dictogloss technique and those who are not in listening comprehension and students’ respond in the implementation of dictogloss technique in improving their listening comprehension. This study was carried out at SMAN 2 Banjar. In this study, the writer used a true-experimental method with pre-test and post-test design. The population was all the students at the eleventh grade of SMAN 2 Banjar. The instruments used for collecting the data were pre-test and post-test in form of listen the spoof text and recontruct it as usual the real text with her/his friend. The students reconstruct the text with their friends based on the note they have taken by listen teachers’ dictation about spoof text. The results of the tests were calculated using the t-test formula to found out a significant difference between pre-test and post-test. The result showed that the value of tobserved was 2.10 and t-table value was 2.00 at significance level of 0.05. In this case, tobserved value was higher than ttable value (2.10>2.00). In conclusion, Dictogloss technique effective in improving students’ listening comprehension because can extend positive influence on students’ listening achievement. The students’ has positive respond to this technique. It can be seen that almost of them agree that Dictogloss technique is appropiate technique for listening comprehension. Based on these findings, it is recommended that when teachers teaching listening they can used dictogloss technique. Keywords: Dictogloss technique, listening comprehension